1988
DOI: 10.1063/1.99760
|View full text |Cite
|
Sign up to set email alerts
|

As-deposited superconducting Y-Ba-Cu-O thin films on Si, Al2O3, and SrTiO3 substrates

Abstract: We have developed an electron beam evaporator designed to deal with the special requirements of thin films of oxide superconductors. The growing surface is sprayed with plasma-excited oxygen while the sources and rate monitors operate in a low background pressure. This allows us to reproducibly grow films of Y-Ba-Cu-O on Si, Al2O3, and SrTiO3 substrates at a substrate temperature of 540 °C which are superconducting without the need for annealing. The resistive transitions of most films show an onset of 90 K an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…In contrast with reports in the literature [5,6,9, 10] we were not able to deposit crystalline 123 films with a thickness less than 1 /~m onto (100) Si. Although Venkatesan et al [9] reported only a slight intermixing of silicon and barium at the Si/123 interface, we have observed interfacial reactions at temperatures lower than those required to deposit crystalline 123.…”
Section: Direct Deposition Of 123 On Si and Sio Econtrasting
confidence: 53%
See 2 more Smart Citations
“…In contrast with reports in the literature [5,6,9, 10] we were not able to deposit crystalline 123 films with a thickness less than 1 /~m onto (100) Si. Although Venkatesan et al [9] reported only a slight intermixing of silicon and barium at the Si/123 interface, we have observed interfacial reactions at temperatures lower than those required to deposit crystalline 123.…”
Section: Direct Deposition Of 123 On Si and Sio Econtrasting
confidence: 53%
“…By using oxygen plasmas even lower preparation temperatures can be achieved [6][7][8]. Although direct deposition of thin film 123 (less than 1 /~m) onto silicon substrates has been reported by several authors [5,6,9,10], the quality of the films is relatively poor. To obtain epitaxial films with high critical temperatures and currents, optimum deposition temperatures are found to be around 750°C and (100) SrTiO 3 substrates should be used Ill,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Lanthanum-deficient La 2/3 MnO 3Ϫ␦ thin films were grown on Al 2 O 3 (11 02) and SrTiO 3 ͑100͒ using electronbeam coevaporation. 11 Our previous studies on La 1Ϫx Ca x MnO 3 and La 1Ϫx K x MnO 3 using the same technique were reported elsewhere. 12,13 In brief, we used two electron beam sources to evaporate La and Mn.…”
mentioning
confidence: 91%
“…Specifically, sometimes just damaged layer on sapphire substrate prevented the growing film to get proper orientation. The X-ray data of depositions on sapphire substrates showed that the growth had no preferable orientation [2]. The X-ray analysis showed that as-deposited films were amorphous [3].…”
Section: Introductionmentioning
confidence: 99%